2018
DOI: 10.1002/ajp.22742
|View full text |Cite
|
Sign up to set email alerts
|

Trauma rates and patterns in specific pathogen free (SPF) rhesus macaque (Macaca mulatta) groups

Abstract: There are some predictable patterns of trauma in captive rhesus macaque (Macaca mulatta) social groups. Several factors have been documented to contribute to these patterns, including group formation of unrelated animals, and the establishment of dominance ranks. Here, we report on how socially induced trauma in groups of rhesus monkeys is influenced by the breeding season, numbers of matrilines per group and matriline size. We analyzed 3 years of data collected from veterinary admittance logs for four groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The authors also report that wounding did not increase during the breeding season as had been previously reported under free‐ranging conditions (e.g., Drickamer, 1975), but instead increased during the birth season. In addition to seasonality and sex, other predictors of wounding in captive groups of rhesus macaques have included sex ratios and conflict intervention behavior (Beisner et al, 2012), and cohesive matrilineal structures (Beisner, Jackson, Cameron, & McCowan, 2011; Stavisky, Ramsey, Meeker, Stovall, & Crane, 2018). These studies contribute to our understanding of the factors that influence wounding in related macaque species, but as of yet, there are no published studies on factors influencing wounding frequencies in our species of interest, Japanese macaques.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also report that wounding did not increase during the breeding season as had been previously reported under free‐ranging conditions (e.g., Drickamer, 1975), but instead increased during the birth season. In addition to seasonality and sex, other predictors of wounding in captive groups of rhesus macaques have included sex ratios and conflict intervention behavior (Beisner et al, 2012), and cohesive matrilineal structures (Beisner, Jackson, Cameron, & McCowan, 2011; Stavisky, Ramsey, Meeker, Stovall, & Crane, 2018). These studies contribute to our understanding of the factors that influence wounding in related macaque species, but as of yet, there are no published studies on factors influencing wounding frequencies in our species of interest, Japanese macaques.…”
Section: Introductionmentioning
confidence: 99%
“…Further, because the sex ratio changed (from 2.6 to 6.6 females per male) between the two studies, the effects of season and sex ratio are confounded in these analyses. We suspect; however, that the change in sex ratio may have had a larger effect on trauma than season because our group‐level analyses showed that total trauma was more frequent during the spring birth season than the fall mating season, which is in contrast to the expected increase in aggression and/or trauma due to mating season competition (Stavisky et al, ; Wilson & Boelkins, ).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, although foraging enrichment may alter aggression frequencies, the impact on socially inflicted traumas is unclear because the rates of aggression do not necessarily predict rates of trauma (Beisner, Wooddell, Hannibal, Nathman, & McCowan, ; Pomerantz & Baker, ; Ruehlmann, Bernstein, Gordon, & Balcaen, ). Rather, trauma can be mediated by other internal (e.g., policing, sex ratio: Beisner, Jackson, Cameron, & McCowan, ; matrilineal fragmentation: Beisner, Jackson, Cameron, & McCowan, ) and external (e.g., season: Stavisky, Ramsey, Meeker, Stovall, & Crane, ) factors. Therefore, the effect of foraging enrichment on trauma outcomes needs to be directly tested.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, social group instability can sometimes lead to matrilineal overthrows (in which related females fight and reverse rank with another group of related females) that can result in severe physical trauma and, in some cases, the death of members of the deposed matrilines 18,19 . Rhesus aggression and wounding are more frequent and more intense in the breeding season with increases in competition for access to breeding partners 20,21 . Coincident with breeding season is the introduction of new males to female social groups in some years, because females are more receptive to the presence of the unfamiliar males at that time 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Rhesus aggression and wounding are more frequent and more intense in the breeding season with increases in competition for access to breeding partners. 20,21 Coincident with breeding season is the introduction of new males to female social groups in some years, because females are more receptive to the presence of the unfamiliar males at that time. 22,23 Therefore, understanding the impacts of MPA treatment on female rhesus social behavior, particularly during introductions of males during the breeding season, is important for maintaining the stability of matrilines in large captive breeding groups, and for mitigating rates of aggression and wounding, which are common concerns among those managing breeding colonies of rhesus macaques.…”
mentioning
confidence: 99%